2022
DOI: 10.3390/jcm11133664
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Radiographic Predictors of Non-Union in Infra-Isthmal Femoral Shaft Fractures after Antegrade Intramedullary Nailing: A Case–Control Study

Abstract: Antegrade intramedullary (IM) nailing is the gold standard treatment for femoral shaft fractures; however, the non-union rate of infra-isthmal femoral shaft fractures is still high after antegrade IM nailing. This retrospective case–control study aimed to determine the association between perioperative radiographic factors and the non-union of infra-isthmal femoral shaft fractures after antegrade IM nailing. Univariate and multivariate analyses were used to evaluate the radiographic risk factors of non-union. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Santolini et al 22 concluded that complex fractures and high initial fracture displacement increased the risk of non-union in long bone fractures. Similarly, Hung et al 23 showed that the risk factors for non-union of femoral shaft fractures were types B and C according to AO/OTA classification, consistent with the results of this study. According to a study on the factors of non-union of shaft fractures by Jensen 24 , type B fractures have a more significant effect on non-union than type A fractures.…”
Section: Discussionsupporting
confidence: 92%
“…Santolini et al 22 concluded that complex fractures and high initial fracture displacement increased the risk of non-union in long bone fractures. Similarly, Hung et al 23 showed that the risk factors for non-union of femoral shaft fractures were types B and C according to AO/OTA classification, consistent with the results of this study. According to a study on the factors of non-union of shaft fractures by Jensen 24 , type B fractures have a more significant effect on non-union than type A fractures.…”
Section: Discussionsupporting
confidence: 92%
“…Antegrade intra-medullary (IM) nailing remains the typical treatment for femoral shaft fractures, yet non-union rates remain high for infra-isthmal femoral shaft fractures based on this approach [32]. Thus, a retrospective case-control study aimed at identifying perioperative radiographic factors linked to non-union in these cases after antegrade IM nailing was performed.…”
Section: Applications Of Image Analysis In Musculoskeletal Imagingmentioning
confidence: 99%